SAT0699 Rapid assessment predicts disease activity improvement in newly diagnosed rheumatoid arthritis (RA). (15th June 2017) - Yates, M; Galloway, J; Snowden, N; Norton, S; Ledingham, JM; Dennison, EM; Rivett, A; Macgregor, AJ
Abstract : Background: Early intervention in RA is associated with improved outcomes in randomised trials. UK guidelines stipulate that those with suspected RA are assessed by a rheumatologist within 3 weeks of referral. However, there are limited real world data confirming the value of early assessment. Previous work suggests social deprivation predicts severe disease at presentation and a worse clinical course (1). The impact of deprivation in early assessment has yet to be characterised on a national level. Objectives: To investigate if rapid assessment in secondary care associates with achieving a good treatment response, and if this is modulated by social deprivation. Methods: An audit, designed as a prospective longitudinal observational study, was conducted to assess early RA care. All NHS providers in England and Wales were required to participate. Follow up data were captured over 3 months for subjects with a diagnosis of RA. Rheumatologist assessment within 3 weeks of referral was the predictor variable. The primary outcome was good EULAR DAS response; the secondary outcome was meaningful improvement in RAID score. Logistic regression was used to estimate for associations. Confounders including age, gender, baseline DAS28 and RAID scores were considered in analyses. The index of multiple deprivation (IMD) rank was calculated for each individual based on super-output geographical areas. The IMD rank was then stratified into quintiles and included as a confounder. Results: 136 of 146 eligible trusts submitted data. 11, 752 subjects consented, 5, 622 were diagnosed with RA. 94/5622 (1.7%) had incomplete assessment date data. DAS28 response was available for 2234/5622 (39.7%), and RAID response for 901/5622 (16%). The table shows baseline characteristics and response for subjects with complete data. Assessment within 3 weeks associated with a significantly greater improvement in DAS28 and RAID scores, with an adjusted odds ratio for a good EULAR response 1.38 (1.15–1.66) and meaningful RAID reduction 1.44 (1.03–2.02). Conclusions: These real world data confirm rapid assessment significantly predicts treatment response, in terms of clinical disease activity and patient reported outcomes. Amongst those who were assessed within 3 weeks of referral, an additional 8% achieved a good EULAR response. The association with RAID response was strengthened when social deprivation was included as a confounder. The relationship between IMD and RAID response appears to be non-linear and requires further study. References: ERAS Study Group. Socioeconomic deprivation and rheumatoid disease:What lessons for the health service? Ann rheum dis. 2000;59(10):794–9. Disclosure of Interest: None declared